2018
DOI: 10.1002/jor.24137
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the hip pistol grip/cam deformity: Origins to joint degeneration

Abstract: This article reviews a body of work performed by the investigators over 9 years that has addressed the significance of cam morphology in the development of hip osteoarthritis (OA). Early hip joint degeneration is a common clinical presentation and preexisting abnormal joint morphology is a risk factor for its development. Interrogating Hill's criteria, we tested whether cam-type femoroacetabular impingement leads to hip OA. Strength of association was identified between cam morphology, reduced range-of-movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 52 publications
(63 reference statements)
0
29
0
2
Order By: Relevance
“…However, a recent study clearly demonstrated the likely interaction between femoral head asphericity and other variables that leads to pathologic impingement, such as acetabular coverage angles, pelvic incidence, and femoral neck/shaft angle. 109 The localized overload of the joint in the region of impingement leads to stiffening of the subchondral bone plate 110 and eventual outside/inside damage of the articular surface. 6 Impingement can also take place when there are extraarticular femoral and/or pelvic deformities such as torsional abnormalities or a prominent AIIS, respectively.…”
Section: Impingementmentioning
confidence: 99%
“…However, a recent study clearly demonstrated the likely interaction between femoral head asphericity and other variables that leads to pathologic impingement, such as acetabular coverage angles, pelvic incidence, and femoral neck/shaft angle. 109 The localized overload of the joint in the region of impingement leads to stiffening of the subchondral bone plate 110 and eventual outside/inside damage of the articular surface. 6 Impingement can also take place when there are extraarticular femoral and/or pelvic deformities such as torsional abnormalities or a prominent AIIS, respectively.…”
Section: Impingementmentioning
confidence: 99%
“…Since surgical management of FAI and other common hip pathologies in young adults can be effective in minimizing the risks of adverse cartilage loading and degeneration 19,61,64,65,70 , more research needs to be done to examine where changes occur first (i.e., subchondral bone, cartilage, or capsule) in response to varying joint morphology and mechanics. This is certainly the case for the zona orbicularis.…”
Section: Overviewmentioning
confidence: 99%
“…Although it has been well established that surgically resecting the cam morphology can delay the pathomechanical process of subchondral bone stiffening 60 , 61 , cartilage degeneration 62 , 63 , and adverse loading 64 , 65 , it was elusive how much the actual morphology or any of the individual surgical stages contributed to these aspects. In what we believe is the only documented in vitro cadaveric study that has examined a well-represented pathological cohort with cam morphologies, Ng et al evaluated a large group of hip specimens with moderate-to-high alpha angles (representative of the symptomatic cam population) from young, male donors 19 .…”
Section: Surgical Managementmentioning
confidence: 99%
“…The set of samples was a group of 10 SmartBone ® samples (lot TT). Tests were run under angular displacement control at a speed of 0.1 • /s according to [6]. All the samples were preconditioned with six preconditioning cycles between a minimum torque value of −600 Nmm and a maximum one of 600 Nmm before the ramp to rupture.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…In general, the need for a total hip replacement occurs when there is damage at the articular cartilage, which can no longer preserve the joint's anatomical integrity and physiological functionality. Indeed, the cartilage can be damaged by bone fractures; bone necrosis; traumas not involving the subchondral bone but disconnecting the bone to the cartilage layer [4]; cyclic minor traumas due to femur-acetabular impingement [5] or CAM lesions [6]; or inflammatory issues such as primary osteoarthritis, metabolic or septic, rheumatoid, or other immunologically based arthritis [7].…”
Section: Introductionmentioning
confidence: 99%